India dark a story of secrets, lies and lost innocence - Murray, Kirsty (UK Templar Publishing, 2012)
Madras, 1910: Poesy Swift and Tilly Sweetrick are caught up in a scandal that will change their lives forever. Singing and dancing across a hundred stages as members of a troupe of Australian child performers, they travel by steam train into the heart of India. But as one disaster follows another, money runs short and tempers fray. What must the girls do to protect themselves, and how many lives will be ruined if they try to break free? Based on a true story, India Dark recreates shifting friendships and loyalties and a clash of innocence versus experience, set against the backdrop of India's.
A Templar Book.
UCWS-3338g donated by Adrienne Maguddayao - May 2018
Keywords: Young adult fiction; Identity (Psychology); Australian fiction